Primary Lymphomas of the Breast: A Review - James, Emily R; Miranda, Roberto N; Turner, Suzanne D (JPRAS open, 2022)
Lymphomas of the breast are rare neoplasms that arise from breast lymphoid tissue and are characterised by neoplastic B or T cells. Breast lymphomas arising from B cells include, but are not limited to, diffuse large B cell lymphoma, follicular lymphoma, extra-nodal marginal zone lymphoma and Burkitt lymphoma. Anaplastic large cell lymphoma (ALCL) is of a T cell origin and both anaplastic lymphoma kinase (ALK)-positive and ALK-negative presentations have been noted in the breast. In addition, there is a more recently identified presentation of ALK-negative ALCL that arises around textured breast implants and is usually confined to a periprosthetic fibrous capsule. Here, we discuss the clinical presentations, histological and immunohistochemical features and treatment options for each type of primary breast lymphoma. We hope that this review will highlight the importance of the timely and accurate diagnosis of breast lymphoma in order to tailor the most appropriate treatment. We also wish to raise awareness of the breast implant-associated lymphomas, with the goal of stimulating work that will aid our understanding of their epidemiology and pathogenesis.
Keywords: breast implants; breast lymphoma; non-Hodgkin lymphoma; breast implant lymphoma; BIA-ALCL